SEX AND SEXUAL ASSAULT IN THE #METOO ERA. Issue 55 (2020) - Arbour, Benjamin H.
Abstract : In a philosophical dialogue, Thomas the traditionalist, Harvey the hedonist, and Eric the economist each discuss their respective views concerning the ethics of human sex acts. In the course of their conversation, it becomes clear that if sex is to be treated like any other pleasure (and therefore enjoyed indiscriminately), it is very difficult to explain what is so bad about rape and/or other forms of sexual assault. Taking any kind of sexual assault to be bad, therefore, requires adopting a more traditional view towards sex.